The performance of US-based emerging market mutual funds - Halil Kiymaz; Koray D. Simsek (Journal of Capital Markets Studies (JCMS), 2017)
Purpose - The purpose of this paper is to examine the performance of US mutual funds that invest primarily in emerging market equities and bonds. Design/methodology/approach - The study adopts the Morningstar classification of mutual funds and uses the Lipper US Mutual Fund Database through FactSet to obtain monthly returns and various metrics for emerging market equity and bond mutual funds covering the period from January 2000 to May 2017. Several descriptive statistics for these funds are reported as well as various risk-adjusted performance measures. Alphas are computed for different sub-periods using different factor models to mitigate potential biases. Findings - The results show that diversified emerging market funds generate some significant alphas for their investors during the study period. Emerging market bond funds, on the other hand, do not provide any significant positive alphas; mostly alphas are negative. An analysis of sub-period performance suggests that these funds do not consistently provide excess returns, showing great variations from one period to another. Originality/value - The emerging market funds provide US investors with an alternative source of exposure for their portfolios. Emerging markets differ from developed markets on a wide range of market and economic characteristics, including size, liquidity, and regulation. This study contributes to the scarce literature on these types of funds and provides a comprehensive performance assessment against various benchmarks during a period that encompasses significant bear and bull markets across the world.
Keywords: G11; G15; G23; 330; Emerging markets; Performance evaluation; Mutual funds; Diversified funds; Bond funds